(untitled) (International Journal of Engineering and Computer Science, 2017)
In recent years, the development and demand of multimedia product is growing increasingly fast. This is a contribution to insufficient bandwidth of network and storage of memory device. When we send any image over the network it consumes more time. This is due to the huge size of the image file as compared to the text file. One more factor, which is security, should be considered while transmission. Compression can reduce the data redundancy to save more hardware space and transmission bandwidth and encryption can provide security. Compression and encryption algorithms can be classified into two main categories: Independent encryption and compression technique and joint encryption and compression technique. Joint encryption and compression technique is employed to enable faster and secured transmission of image data.